2006
DOI: 10.1063/1.2360278
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of niobium and tantalum neutral clusters with low pressure, unsaturated hydrocarbons in a pickup cell: From dehydrogenation to Met-Car formation

Abstract: Neutral niobium and tantalum clusters (Nbn and Tan) are generated by laser ablation and supersonic expansion into a vacuum and are reacted in a pickup cell with various low pressure (approximately 1 mTorr) unsaturated hydrocarbons (acetylene, ethylene, propylene, 1-butene, 1,3-butadiene, benzene, and toluene) under nearly single collision conditions. The bare metal clusters and their reaction products are ionized by a 193 nm laser and detected by a time of flight mass spectrometer. Partially and fully dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
(66 reference statements)
1
32
0
Order By: Relevance
“…Indeed, experiments in a low pressure pickup cell have shown that total dehydrogenation occurs for the first three C 2 H 2 molecules attached to the neutral Nb 5 cluster. 27 PIE spectra are recorded by monitoring the signal of each species as a function of photon energy. The shoulders present on the peaks due to oxide contamination were not included in the integration.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, experiments in a low pressure pickup cell have shown that total dehydrogenation occurs for the first three C 2 H 2 molecules attached to the neutral Nb 5 cluster. 27 PIE spectra are recorded by monitoring the signal of each species as a function of photon energy. The shoulders present on the peaks due to oxide contamination were not included in the integration.…”
Section: Resultsmentioning
confidence: 99%
“…There is no buffer gas to stabilize the intermediates in the pickup cell so M n A either directly dissociates ͑M n + A͒, undergoes further reactive dissociation ͑C + D , C and D A͒, or is detected in a metastable state. 20 Consequently, the chemistry in a pickup cell occurs at a much higher temperature ͑T ϳ 700 K͒ than that in a flow tube reactor ͑T ϳ 300 K͒.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of neutral Ta clusters with hydrocarbons and N 2 has been studied. [22][23][24] The ionization potentials of neutral Ta clusters are known from photoionization studies. 25 Raman spectra have been measured for Ta 2−4 in an argon matrix.…”
Section: Introductionmentioning
confidence: 99%